2021
DOI: 10.5195/ijt.2021.6380
|View full text |Cite
|
Sign up to set email alerts
|

Telepractice in School-age Children Who Stutter: A Controlled Before and After Study to Evaluate the Efficacy of MIDA-SP

Abstract: The COVID-19 pandemic necessitated a general reorganization of rehabilitation services in Italy. The lockdown in Italy led to the use of telepractice for the delivery of speech therapy, including stuttering. The aim of the present work was to evaluate the effectiveness of the MIDA-SP (Tomaiuoli et al., 2012), delivered online for school-age children who stutter. A non-randomized controlled pre- and post-treatment study included an experimental group (11 children) receiving a telepractice adaptation of MIDA-SP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Appendix C shows four studies with more than 10 children that measured impacts of stuttering using the OASES, with substantial treatment effects reported in the range of around 20-25% improvement posttreatment, and the one follow-up reported showing an improvement of 33%. The Tomaiuoli et al (2021) intervention was associated with positive change for the domain of stuttering impact. However, beyond that, little can be said about any individual procedures that may have contributed to that effect because it was a hybrid treatment, which involved 'principles and strategies from both the stuttering modification and fluency shaping approaches' including procedures 'to reduce fear, anxiety, and other negative emotions and thoughts about stuttering' (2).…”
Section: F I G U R E 1 Study Screening Processmentioning
confidence: 91%
See 1 more Smart Citation
“…Appendix C shows four studies with more than 10 children that measured impacts of stuttering using the OASES, with substantial treatment effects reported in the range of around 20-25% improvement posttreatment, and the one follow-up reported showing an improvement of 33%. The Tomaiuoli et al (2021) intervention was associated with positive change for the domain of stuttering impact. However, beyond that, little can be said about any individual procedures that may have contributed to that effect because it was a hybrid treatment, which involved 'principles and strategies from both the stuttering modification and fluency shaping approaches' including procedures 'to reduce fear, anxiety, and other negative emotions and thoughts about stuttering' (2).…”
Section: F I G U R E 1 Study Screening Processmentioning
confidence: 91%
“…The Tomaiuoli et al. (2021) intervention was associated with positive change for the domain of stuttering impact. However, beyond that, little can be said about any individual procedures that may have contributed to that effect because it was a hybrid treatment, which involved ‘principles and strategies from both the stuttering modification and fluency shaping approaches’ including procedures ‘to reduce fear, anxiety, and other negative emotions and thoughts about stuttering’ (2).…”
Section: Main Contributionsmentioning
confidence: 95%
“…People who have been diagnosed with speech-language disorders can participate in a variety of speech therapies in an effort to alleviate some of the sufferings they experience as a result of having these disorders. Different techniques from the field of speech-language therapy are employed in order to diagnose and successfully treat speech disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telepractice allows speech therapists to deliver their services remotely rather than in person. The World Health Organization (WHO) defines telepractice as the delivery of clinical and rehabilitation services by means of information and communication technology (ICT) with the assistance of telephones, mobile applications, and other videoconferencing platforms in settings in which the patients and their treating physicians are geographically separated from one another over a range of distances, both short and long [ 3 , 4 , 7 , 9 ]. In light of the current COVID-19 pandemic, the purpose of this review article is to study the usefulness of using telepractice for speech-language therapy and to discuss potential next steps in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Looking closely at the TP stuttering management research on both adults and children, several studies have investigated therapy outcomes using TP in delivering the Lidcombe Program for pre‐school children (Bridgman et al., 2016; Harrison et al., 1999; Lewis et al., 2008; O'Brian et al., 2014; Van Eerdenbrugh et al., 2018), different therapy approaches for school‐age children (Ryer & Poll, 2020; Tomaiuoli et al., 2021), and the Camperdown Program for adults (Carey et al., 2010; Erickson et al., 2016; O'Brian et al., 2008), suggesting that TP is an efficacious model for delivering stuttering therapy. Unfortunately, although assessment is the first step before management, to date not a single study can be found in which the viability of TP stuttering assessments of children is evaluated (Lowe et al., 2013; McGill et al., 2019).…”
Section: Introductionmentioning
confidence: 99%